Efeitos da diatomita em substituição parcial ao cimento portland nas propriedades de concretos convencionais - Macedo, Amanda Regina de Souza (2022)
Concrete is a composite, considered the most used construction material in the world. Its main component is Portland cement, responsible for the formation of calcium silicate hydrates (C-S-H) formed during hydration and which are mainly responsible for the compressive strength of concrete. However, currently, the search for alternative, more sustainable materials has increased, aiming to reduce CO2 emissions and consequently minimize environmental impacts. This is possible through the use of supplementary cementitious materials (SCMs), which can be used as a substitute for clinker in the manufacture of Portland cement and/or as an addition or replacement for cement in the production of concrete. Diatomite is considered a natural MCS, which with high SiO2 concentration is able to react with calcium hydroxide (CH) released during cement hydration to produce additional calcium silicate hydrate (C-S-H). Thus, the present work aimed to study the effects of replacing Portland cement by diatomite in the proportions of 0%, 10%, 15% and 20% by volume, in the production of conventional concretes with fck estimated at 30MPa (NBR 8953, 2015). Initially, the starting materials were characterized as to their physical, chemical, mechanical, structural and microstructural properties. Then, concretes were produced with a volume ratio of 1: 1.33:2.33 and a/c ratio=0.44. The concretes were evaluated for their properties in the fresh state (slump test) and in the hardened state (compressive strength, porosity, water absorption, capillary water absorption and chloride ion diffusion). Cement pastes with the same proportions of the concretes were analyzed by XRD (X-ray diffraction) and TG/DTA (thermogravimetry) techniques at 7, 28 and 91 days. The results showed that the incorporation of diatomite caused a small reduction in the values of compressive strength of the concretes. Nevertheless, the concretes produced with 15%v. and 20%v. of diatomite presented a higher evolution in the values of compressive strength (20.07% and 16.16%, respectively) from 28 to 91 days, as a consequence of the pozzolanic reaction. While the 0%v. and 10%v. concretes presented an evolution of 4.33% and 5.20%, respectively. This observation was confirmed in the results of XRD and TGA, where it was observed that there is a greater consumption of portlandite and a greater amount of combined water in pastes with diatomite incorporation. The total porosity, water absorption and capillary absorption decreased in the concrete with 10%v. of diatomite, due to the filler effect. The incorporation of diatomite reduced the chloride ion diffusion coefficient of the concretes due to the refinement of the pore structures, presenting the following values 8.389 x 10-12; 5.668 x 10-12 ; 2.241 x 10-12 ; 1.297 x 10-12 , respectively, for the concretes CD-0, CD-10, CD-15 and CD-20.